Update on Transcatheter Tricuspid Valve Replacement Therapies - Goldberg, Ythan H.; Ho, Edwin; Chau, Mei; Latib, Azeem (Frontiers in Cardiovascular Medicine, 2021)
Severe tricuspid regurgitation is relatively common, especially in the elderly, and portends poor survival. Neither medical therapy nor conventional surgery is efficacious for most patients. In contrast, transcatheter tricuspid valve interventions are showing promise to improve quality of life and mortality. Although there is more clinical experience with transcatheter tricuspid valve repair, there are many patients for which repair is either not possible or cannot optimally reduce the severity of tricuspid regurgitation. Transcatheter tricuspid valve replacement is rapidly emerging and may ultimately become the preferred treatment option. In this review, we discuss transcatheter tricuspid valve replacement, analyze the devices in development and in clinical trials, and highlight the advantages and drawbacks of transcatheter tricuspid valve replacement vs. repair.